RITUAL BEDEKEH DAN KEPERCAYAAN SUKU AKIT DI PROVINSI RIAU - Suroyo Suroyo; Neni Hermita; Bedriati Ibrahim; Bima Maulana Putra (Jurnal Lektur Keagamaan, 2022)
ABSTRACT Bedekeh is a medical tradition passed down from generation to generation in the Akit tribe aiming at curing a person's illness. Bedekeh ritual contains cosmological and religious ideology regarding human relationship with Akit ancestors, God and human relationship with other forces beyond human ability. This ritual is dedicated to the ancestral gods as an aid in one's treatment. The ritual is led by Batin (Bomoh or big shaman). This study employs a qualitative technique with a cultural studies approach to explore Bedekeh in the Akit tribal community in relation to Islam. The study found that in the Bedekeh ritual, when someone enters a state of trance (possessed), various spirits such as the Islamic spirit (Hantu Islam), the Malay spirit (Malay ghost), and others appeared, and then helped and communicated according to the mantra that was chanted when entering the body. The original Malay community who embraced Islam rejected the local tradition of the Bedekeh ritual because it was considered to contain animistic teachings that were shirk, idolatrous, and heretical. The people of the Akit tribe are often positioned as the outermost area (periphery) and are placed in a low position and the lowest social status. The construction of such social structures still affects the Malay community and the Muslim Malay community until today.  Keywords: Akit tribe, bedekeh, belief, cultural studies, ritual    ABSTRAK Bedekeh merupakan tradisi pengobatan yang diturunkan dari generasi ke generasi pada masyarakat suku Akit dengan tujuan untuk menyembuhkan penyakit pada diri seseorang. Ritual bedekeh mengandung ideologi kosmologi dan ideologi religius mengenai hubungan manusia dengan leluhur Akit, Tuhan dan keselarasan manusia dengan kekuatan-kekuatan lain di luar kemampuan jangkauan pikiran manusia. Ritual ini dipersembahkan untuk dewa-dewa leluhur yang akan dipanggil sebagai penolong dalam pengobatan seseorang yang dipimpin oleh Batin (Bomoh atau dukun besar). Penelitian ini menggunakan teknik kualitatif dengan pendekatan cultural studies untuk mengungkap Bedekeh pada masyarakat suku Akit dalam kaitannya dengan Islam. Hasil penelitian menunjukkan bahwa dalam ritual Bedekeh dan dalam keadaan trance (kerasukan), maka muncul berbagai roh seperti roh Islam (Hantu Islam), roh Melayu (hantu Melayu), dan lain-lain yang membantu dan berkomunikasi sesuai dengan mantra yang dilantunkan saat memasuki tubuh Batin. Masyarakat Melayu asli yang memeluk Islam menolak tradisi lokal ritual Bedekeh karena dianggap mengandung ajaran animisme yang bersifat syirik, musrik, dan sesat. Masyarakat suku Akit sering diposisikan sebagai area terluar (periferi) dan menempatkan pada posisi yang rendah dan derajat sosial terendah. Konstruksi struktur sosial yang demikian masih memengaruhi masyarakat Melayu dan Masyarakat Melayu Muslim hingga sekarang.  Kata kunci: bedekeh, kepercayaan, suku Akit, ritual